Hemolytic disease of the fetus and newborn: rapid review of postnatal care and outcomes - Derek P. de Winter; Allysen Kaminski; May Lee Tjoa; Dick Oepkes; Enrico Lopriore (BMC, 2023)
Abstract Background Advances in postnatal care for hemolytic disease of the fetus and newborn (HDFN) have occurred over the past decades, but little is known regarding the frequency of postnatal treatment and the clinical outcomes of affected neonates. Most studies reporting on HDFN originate from high-income countries or relatively large centers, but important differences between centers and countries may exist due to differences in prevalence and available treatment options. We therefore aimed to evaluate the postnatal treatment landscape and clinical outcomes in neonates with Rhesus factor D (Rh(D))- and/or K-mediated HDFN and to provide recommendations for future research. Methods We conducted a rapid literature review of case reports and series, observational retrospective and prospective cohort studies, and trials describing pregnancies or children affected by Rh(D)- or K-mediated HDFN published between 2005 and 2021. Information relevant to the treatment of HDFN and clinical outcomes was extracted. Medline, ClinicalTrials.gov and EMBASE were searched for relevant studies by two independent reviewers through title/abstract and full-text screening. Two independent reviewers extracted data and assessed methodological quality of included studies. Results Forty-three studies reporting postnatal data were included. The median frequency of exchange transfusions was 6.0% [interquartile range (IQR): 0.0-20.0] in K-mediated HDFN and 26.5% [IQR: 18.0-42.9] in Rh(D)-mediated HDFN. The median use of simple red blood cell transfusions in K-mediated HDFN was 50.0% [IQR: 25.0-56.0] and 60.0% [IQR: 20.0-72.0] in Rh(D)-mediated HDFN. Large differences in transfusion rates were found between centers. Neonatal mortality amongst cases treated with intrauterine transfusion(s) was 1.2% [IQR: 0-4.4]. Guidelines and thresholds for exchange transfusions and simple RBC transfusions were reported in 50% of studies. Conclusion Most included studies were from middle- to high-income countries. No studies with a higher level of evidence from centers in low-income countries were available. We noted a shortage and inconsistency in the reporting of relevant data and provide recommendations for future reports. Although large variations between studies was found and information was often missing, analysis showed that the postnatal burden of HDFN, including need for neonatal interventions, remains high. Systematic review registration PROSPERO 2021 CRD42021234940. Available from:  https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021234940 .